Space Transformation in Residential House Small Entrepreneurs Banana Sale - Rinaldi Mirsa; Muhammad Muhammad; Fidyati Fidyati; Eri Saputra; Muhammad Rumiza (International Journal of Engineering, Science and Information Technology, 2021)
Space transformation occurs in line with the needs and availability of resources owned by space users. The arrangement and utilization of space is carried out to optimize the function of the space owned and the limited space owned by the space user requires an adjustment in the use of the space owned to achieve business goals as well as the comfort of the living environment. Pante Bidari is a banana sale    producing area in Aceh, which is located in East Aceh Regency, where the majority of the people work as small entrepreneurs and   workers in the Banana Sale Industry. The process carried out when producing Pisang Sale uses a special room consisting of a storage room, peeling room, sale room and packaging room. This study aims to determine how the transformation of space in a small banana sale house. The method used in this research is a qualitative method. This study found that the spatial transformation that occurred in the small businessman's house of Pisang Sale in Pante Bidari District, East Aceh Regency is one way to optimize the utilization and utilization of space, so that the Pisang Sale production room consists of storage room, stripping room, sale room and packaging room. using residential space as an aspect of activity in residential homes, so that ongoing activities are not disturbed by other activities, residential space in terms of space dimensions there are changes that include addition, reduction and movement of space aimed at adjusting space requirements. Judging from the spatial relationship, there are several spaces that are far from each other and close to each other, so that access to activities carried out can optimize the function of the space.